Maltol, a Natural Flavor Enhancer, Inhibits NLRP3 and Non-Canonical Inflammasome Activation - Huijeong Ahn; Gilyoung Lee; Byung-Cheol Han; Seung-Ho Lee; Geun-Shik Lee (Antioxidants, 2022)
Maltol (3-hydroxy-2-methyl-4-pyrone) is used widely as a food and cosmetic supplement, and it has antioxidant and anti-inflammatory activities. Inflammasome causes the maturation and secretion of interleukin (IL)-1β and -18 through the activation of caspase-1 (Casp1), which contributes to various inflammatory diseases. This study examined the effects of maltol on the inflammasome activation in macrophages and mice. Lipopolysaccharide (LPS)-primed macrophages were treated with a trigger of NLRP3, NLRC4, AIM2, or non-canonical (NC) inflammasomes in the presence of maltol. The secretion of IL-1β and IL-18 and the cleavage of Casp1 were analyzed as indices of inflammasome activation. Mice were injected with LPS and an NLRP3 trigger with or without maltol, and the peritoneal IL-1β secretions were observed. The effects of maltol on reactive oxygen species (ROS) production and Casp1 activity were analyzed to determine the mechanism. Maltol inhibited the activation of NLRP3 and NC inflammasomes, but it did not alter the other inflammasomes. Maltol also attenuated IL-1β secretion resulting from the inflammasome activation in mice. The anti-inflammatory mechanism of maltol was revealed by the inhibition of ROS production and Casp1 activity. Maltol is suggested to be promising as a anti-inflammasome molecule.